POST-POSITIVISM INOVATIONS ON BRAZILIAN ADMINISTRATIVE LAW PRINCIPLES - Luciana Gaspar Melquiades Duarte; Gabriel Coutinho Galil (Revista Eletrônica do Curso de Direito da UFSM, 2017)
The justification of this paper is the mismatch between a great part of the Brazilian Administrative Law literature and the new scientific referential brought by Post-Positivism, and its proposal is to review the main principles of the Administrative Theory under the post-positivist perspective, mainly guided by Robert Alexy’s and Ronald Dworkin’s work. Thus, through the deductive research method, the four core pillars of Administrative Law were historically and scientifically reviewed: the legality principle, the supremacy of public interest principle, the administrative discretion and the administrative act. By this effort, it suggest the adaptation of the referred pillars to the constitutional principles and the consolidation of the Democratic State of Law.